KEPENTINGAN INDONESIA BERGABUNG DENGAN IRENA (INTERNATIONAL RENEWABLE ENERGY AGENCY) TAHUN 2014 - Zulfadli "; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research will explain about Indonesia interest joined with IRENA ( International Renewable Energy Agency). Nowadays energy condition is so far from standart of energy endurance. Indonesia energy needs still dominated by fossil energy. In 2013, Fossil Energy produces 93,4% of energy consumtion, 5,7% by renewable energy. 7% oil, 20,1% gas, 24,5% from coal. With Indonesia energy endurance and global market that affected domestic energy condition, Indonesia need to comply the national interest about energy endurance an as an active role actor in international relation.This research using realism perspective from international relation study with supporting theory is the national interest from Morgenthau. This research using nation-state as analysis level that analize Indonesia policy about its relation between other state. This research is based on fact, data, argument and theoretical analize with qualitative-explanative method.This research answering the question about hypotesys that Indonesia interest is developing renewable energy, human resource empowerment, exploration, exploitation, and managing resource of renewable energy, and Indonesia count on investment excalation of renewable energy sector.Accomplishing this interest Indonesia takes a policy to joined IRENA, because IRENA facilitate every member state that joined IRENA in renewable energy sector.Keyword: Energy Endurance, Fossil Energy Crissis , IRENA, National Interest, Renewable Energy.